Evaluation of awareness about pharmacoeconomics in postgraduate students of a tertiary care teaching hospital: a questionnaire based observational study - Gupta, Rohini; Malhotra, Pavan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pharmacoeconomics identifies, measures and compares the costs and consequences of drug therapy to health care systems and society. The per capita income of all middle class people is limited and the drug prices are growing extensively. Therefore, it is the responsibility of the health-care professionals to balance both cost and quality of treatment. Hence, this study was planned among the postgraduate students who form the major part of health care delivery system to assess their awareness about pharmacoeconomis. Methods: This was a questionnaire based cross-sectional study. Self-administered questionnaire was distributed among 72 residents, out of which 61 completely filled questionnaires were finally used for statistical analysis. The questionnaire contained questions relating to awareness, knowledge, method of application and students’ attitude about pharmacoeconomics. Results: The willingness to participate in the study among postgraduates was extremely poor. Those who have participated, almost 39% of participants were having awareness about the topic. Nearly 31 % of the participants were having knowledge regarding pharmacoeconomics and around 21 % of participants have learnt the method of application in various aspects. Conclusions: Study has revealed that that the knowledge and perception level of postgraduates in day to day use of pharmacoeconomic concepts are poor and limited. Therefore, it is very necessary to make them aware about the concept of pharmacoeconomics by incorporationg it in their medical curriculum and by conducting CMEs and Workshops on pharmacoeconomics.